Variáveis abióticas e espécie nativa competidora relacionadas ao sucesso de uma macrófita submersa invasora em diferentes escalas espaciais. - Pulzatto, Mikaela Marques (2018)
The success of invasive species depends on the overcoming of physiological and biotic filters as these species pass through the invasion stages. Abiotic variables likely have greater relative importance over invasive at large spatial scales, while biotic interactions are more important on fine scales. Anthropogenic disturbances, such as reservoirs, may facilitate the process of invasion by submerged aquatic macrophytes. In this study, we evaluated the relative importance of the abiotic factors and of a competitive native species on the performance of the invasive submerged macrophyte Hydrilla verticillata. Samplings were conducted in two spatial scales (macrophytes patch and quadrat) to evaluate how the relative importance of the abiotic factors and the competitive native vary between scales. The relative abundance (large scale) and biomass (fine scale) of hydrilla and the competing species were collected along with environmental variables in a large subtropical reservoir. Bayesian Generalized Linear Models and a selection of models using the Akaike Information Criterion were used. At large scale, the abiotic variables maximum fetch (positive correlation), turbidity and conductivity (negative correlation) were the most important to explain the hydrilla abundance, while littoral slope and competitive native species (positive correlation) presented less relative importance. At fine scale, both abiotic variables, alkalinity and total organic matter of the sediment, and competitive native species (negative correlation) were the most important. Depth, turbidity and maximum fetch exhibited less relative importance. Our results suggest that at the large scale the strength of biotic interactions decreases as the variation of environmental conditions increases, indicating greater importance of abiotic factors. At the small scale, most individuals have the potential to interact directly with each other, evidencing the importance of biotic interactions. However, in aquatic environments, biotic resistance is generally less important than environmental resistance, indicated in this study by the great importance of abiotic variables even in fine scale. Environmental heterogeneity may explain the positive correlation between native and invasive on a large scale, while the negative correlation in restricted scale suggests the effect of competition. In synthesis, we show that the abiotic factors that explain the invasion success of a submerged invasive macrophyte are basically the same in two spatial scale, but the importance of biotic interactions changed with scale. Thus, our data suggest that spatial scales must be taken into account in models to explain the success of invasive macrophytes.